A Smart Crop-Based Irrigation System With Automated Pump Control. - K, Manikandan; Banu, Sumaya; Jeganath, Jeganath; Jeganath, Jeganath; S, Cibin; Rohan, Rohan; Krishna, Shreyas; Vignesh, V. (Journal of Neonatal Surgery, 2025)
Water scarcity and inefficient irrigation practices are among the most pressing challenges in modern agriculture. Traditional irrigation systems, which rely on manual scheduling and fixed watering cycles, often result in water wastage, suboptimal crop hydration, and unnecessary energy consumption. In response to these challenges, smart irrigation technologies leveraging Internet of Things (IoT), real-time soil moisture monitoring, and weather-based automation have emerged as effective solutions for precision agriculture. This study presents a comprehensive review of automated irrigation systems with a focus on intelligent pump control, data-driven decision-making, and sensor-based water management. The proposed smart irrigation framework integrates soil moisture sensors, weather prediction models, and automated pump control mechanisms to optimize water distribution based on real-time environmental conditions. By incorporating wireless communication technologies (WiFi, GSM, and LoRa), cloud-based data processing, and AI-driven analytics, these systems ensure efficient irrigation scheduling, reducing water waste and improving crop yields. The automation of irrigation using microcontroller-based systems, such as Arduino and Raspberry Pi, enhances precision by dynamically adjusting water supply based on real-time soil and atmospheric parameters. This paper systematically categorizes modern smart irrigation techniques, analyzing their benefits, limitations, and implementation challenges. Various sensor technologies, including soil moisture probes, temperature sensors, and humidity detectors, are reviewed in terms of accuracy, response time, and scalability. Additionally, weather-based irrigation models, which use meteorological data to forecast water requirements, are explored for their potential in enhancing irrigation efficiency. The integration of cloud computing for data storage and remote access further improves decision-making capabilities, enabling farmers to monitor and control irrigation systems from anywhere. While smart irrigation offers significant advantages, several technical and practical challenges remain. Sensor calibration issues, data transmission delays, hardware costs, and system scalability pose barriers to widespread adoption. Furthermore, reliability under extreme weather conditions and energy efficiency, particularly in off-grid farming regions, are key considerations for future development. The incorporation of renewable energy sources, such as solar-powered irrigation pumps, can enhance system sustainability. Additionally, the use of blockchain technology for data security and AI-driven predictive analytics can further improve irrigation automation. This study identifies emerging trends and future research opportunities in automated precision irrigation, emphasizing the role of machine learning, big data analytics, and IoT-based smart farming in transforming agricultural water management. By integrating advanced sensor networks, intelligent automation, and cloud-based remote monitoring, smart irrigation systems have the potential to revolutionize sustainable agriculture and ensure efficient resource utilization. This review serves as a valuable resource for researchers, engineers, and policymakers interested in advancing next-generation irrigation technologies for enhanced agricultural productivity.